Masters of silence - Kacer, Kathy, 1954- (Kacer, Kathy, 1954- Heroes quartet., 2019)
A historical fiction book about childhood of the internationally famous mime Marcel Marceau. To escape the encroaching Nazi army, siblings Henry and Helen are shuttled to a French convent where their mother promises to return and retrieve them, but until she does, they must assume new identities. Henry, traumatized, goes silent. It's only when he meets a local mime that he learns to find his voice again and help he and his sister heal.